2017
DOI: 10.1080/15332640.2017.1300554
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic variation in mental health correlates of substance use among college students

Abstract: This study investigated mental health indicators, substance use, and their relationships, by race/ethnicity. A probability sample of 1,053 students at two California universities self-reported their frequency of substance use and rated their experience with indicators of mental health. One-way analysis of variance (ANOVA), chi-square tests, and multivariate censored regression models were estimated to examine which indicators of mental health were associated with each substance use form by race/ethnicity. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In an extension of previous research, the present study examined whether negative affect (i.e., stress, depressive and anxiety symptoms) relate to alcohol and marijuana outcomes (use quantity and negative consequences) via alcohol and marijuana use motives similarly among a large group of dual college student users (past 30-day use; not necessarily simultaneous use). Given that prior investigations of mood and anxiety-related symptoms in relation to substance use among college students has revealed differential associations depending on the substance(s) used and the frequency, severity, and comorbidity of other mental health symptoms (Sumstine, Cruz, Schroeder, Takeda, & Bavarian, 2017;Shafer, Koenig, & Becker, 2017), we examined three independent models (one for each negative affect symptom). Based on previous findings, we expected that negative affect symptoms would primarily be associated with higher coping motives for both substances; which in turn would be associated with higher negative alcohol and marijuana-related consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In an extension of previous research, the present study examined whether negative affect (i.e., stress, depressive and anxiety symptoms) relate to alcohol and marijuana outcomes (use quantity and negative consequences) via alcohol and marijuana use motives similarly among a large group of dual college student users (past 30-day use; not necessarily simultaneous use). Given that prior investigations of mood and anxiety-related symptoms in relation to substance use among college students has revealed differential associations depending on the substance(s) used and the frequency, severity, and comorbidity of other mental health symptoms (Sumstine, Cruz, Schroeder, Takeda, & Bavarian, 2017;Shafer, Koenig, & Becker, 2017), we examined three independent models (one for each negative affect symptom). Based on previous findings, we expected that negative affect symptoms would primarily be associated with higher coping motives for both substances; which in turn would be associated with higher negative alcohol and marijuana-related consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Our comparison-group participants (not included in the current analytic sample) were significantly more diverse (Papp et al, 2020). Sumstine et al (2018) explored racial and ethnic variation in mental health correlates of multiple forms of substance use among students sampled from two colleges in California. Focusing on problematic prescription behaviors, their results found that White students had the highest rates of prescription stimulant and pain medication misuse, although students from Asian, Latino, and “all other” backgrounds also reported misuse rates that were higher than the national average.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on problematic prescription behaviors, their results found that White students had the highest rates of prescription stimulant and pain medication misuse, although students from Asian, Latino, and “all other” backgrounds also reported misuse rates that were higher than the national average. Racial and ethnic differences in associations between mental health symptoms and prescription misuse were identified; for example, White and Latino (but not Asian) students who scored higher on inattention were more likely to report misuse of stimulant medications (Sumstine et al, 2018). Other recent work based on highly disadvantaged populations found that unmet mental health needs and suicidal feelings were associated with recent prescription drug misuse among a U.S.-based sample of homeless young adults (Barman-Adhikari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Third, our sample was relatively homogeneous and included an overrepresentation of White participants and females. Our study does not address stress contexts that have been associated with young adult substance use in prior work, including minoritised identities such as LGBTQ (Felner et al., 2020) and racial and ethnic (Sumstine et al., 2018) statuses. Thus, the generalisability of our findings is limited.…”
Section: Discussionmentioning
confidence: 99%